Metode Omnibus Dalam Pembentukan Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Cipto Kuncoro (Universitas Islam Darul Ulum, 2023)
The birth of a legal product in the form of Law Number 11 of 2020 concerning Job Creation has led to disagreement with its enactment by taking the judicial review route to the Constitutional Court. The decision stated that it was contrary to the 1945 Constitution of the Republic of Indonesia and did not have conditionally binding legal force as long as it was not interpreted as